(untitled) (Journal of Foreign Language Studies, 2021)
Synonymy is a popular phenomenon in teaching and learning foreign languages in general and Russian language in particular. Such phenomenon offen poses difficulties for learners in choosing expressions to sound like natives during communication. Therefore, on the basis of scientific research and practical teaching experience, this paper proposes some principles for teaching synonymy to Vietnamese learners.